LATIN AMERICA: COMMODITIES CYCLE AND THE CRISIS OF GLOBAL CAPITALISM - Corsi, Francisco Luiz; Santos, Agnaldo dos Santos; Camargo, José Marangoni Camargo Marangoni (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This article aims to discuss the impacts of the commodity boom in Latin American economies. We will discuss the boom and its crisis within the contradictory and unstable process of globalization of capital characterized, among other things, by the hegemony of financial capital and by the spatial reconfiguration of capital accumulation, which has an enormous influence on the periphery of the system and the reorganization of the international division of labor. The paths pursued by the Latin American economies are part of this process. Thus, the analysis of the possibilities and obstacles to an inclusive economic and social development has to start from this frame of reference.